Diversification strategy and performance of Malaysian firms / Wan Mohd Nazri Wan Daud, Norhana Salamudin and Ismail Ahmad - Wan Daud, Wan Mohd Nazri; Salamudin, Norhana; Ahmad, Ismail (Universiti Teknologi MARA Cawangan Pahang, 2006)
Business diversification has drawn the attention of strategic management and finance scholars. This preliminary study examines factors that influence firm performance using multiple measures of performance namely accounting and market measurements. The study used OLS data analysis for a sample of 70 Malaysian firms from various industries during the period 2001 to 2005. The evidence produces some factors that explain performance measurement but results are still ambiguous.